No Surprises, Please: Voting Costs and Electoral Turnout - Jean-Victor Alipour; Valentin Lindlacher (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study how shocks to voting costs affect electoral turnout. Individuals whose polling place is relocated face changes to their cost of voting in person due to altered distance and unfamiliarity with the new polling place. Using address-level and precinct-level data, we find that polling place relocations depress turnout by 0.5–0.6 percentage points (p.p.): in-person turnout declines by 0.8–1.1 p.p. and is only partly compensated by a 0.3–0.5 p.p. increase in mail-in voting. However, the drop in turnout is only transitory as mail-in votes balance the decline in in-person votes in subsequent elections. This finding is consistent with inattentiveness to relocations, causing individuals to miss the deadline for requesting mail-in ballots. Some inattentive voters forgo voting today but turn to mail-in voting in ensuing elections. Our results are in line with rational choice models of voting and incompatible with the hypothesis that voting is habit forming.
Keywords: D72; D73; D83; R41; 330; voter turnout; habit formation; elections; election administration; precincts; polling places